Precipitate dissolution and grain growth in the heat affected zone of HSLA-100 steel - Shome M.; Sarma D.S.; Gupta O.P.; Mohanty O.N. (My University, 2025)
An attempt has been made to predict the dissolution of Nb(CN) precipitates in the heat affected zone (HAZ) of a Nb containing HSLA-100 steel. An invariant size approximation model along with existing solubility product data have been applied to continuous heating and cooling situation to ascertain the kinetic strengths from heat input-peak temperature conditions at which dissolution of precipitates take place. Peak temperatures beyond which precipitates rapidly dissolve and cause grain growth have been identified, and they are in consonance with the austenite grain growth data.